Water-based zinc ion battery electrolyte added with humectant and application of water-based zinc ion battery electrolyte

By adding moisturizer to the zinc-ion battery electrolyte, dendrite, hydrogen evolution and corrosion problems in aqueous zinc-ion batteries are solved, uniform deposition of zinc and battery stability are achieved, battery life is extended and Coulomb efficiency is improved.

CN119297438APending Publication Date: 2025-01-10NANTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411692246.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There are harmful side reactions such as dendrite, hydrogen evolution and metal corrosion in aqueous zinc ion batteries, which limit the cycle life and safety of the battery.

Method used

Add a moisturizer to the zinc ion battery electrolyte to form a protective film by adsorbing moisture at the electrode interface, inhibiting dendrite growth and hydrogen evolution reaction, and guiding uniform deposition of zinc.

Benefits of technology

It significantly improves the cycling performance and stability of zinc ion batteries, extends battery life, and improves Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297438A_ABST
    Figure CN119297438A_ABST
Patent Text Reader

Abstract

The invention provides an aqueous zinc ion battery electrolyte added with a humectant and application of the aqueous zinc ion battery electrolyte. According to the technical scheme, the electrolyte comprises water, zinc salt and a humectant, wherein the humectant binds the water in the electrolyte; the humectant is selected from one or more of a micromolecular humectant and a macromolecular humectant; the macromolecular humectant is selected from one or more of hyaluronic acid, a polysaccharide humectant, a polypeptide humectant and polyethylene glycol; the polypeptide humectant is selected from collagen. The wetting agent has the beneficial effects that the wetting agent has the effects of absorbing moisture, locking water and forming a film, and can be used for constraining water in an electrolyte, inhibiting side reactions in the zinc ion battery, changing the deposition morphology of zinc and guiding uniform deposition of zinc, so that the cycling stability and coulombic efficiency of the zinc ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion battery electrolyte added with a humectant and application thereof. Background Art

[0002] Zinc batteries, especially aqueous zinc-ion batteries, as an emerging rechargeable battery technology, have attracted much attention due to their high safety and high element abundance. However, as the main component of the electrolyte, water brings convenience to zinc batteries, but also brings a series of significant hazards. At present, the zinc negative electrode of aqueous zinc-ion batteries has serious harmful side reactions such as dendrites, hydrogen evolution and metal corrosion in the aqueous electrolyte, which limits the cycle life of the battery and hinders the large-scale application of aqueous zinc-ion batteries. Dendrites refer to the uneven deposition of zinc ions on the zinc negative electrode during the charge and discharge process, resulting in the appearance of dendritic metal zinc crystals on the negative electrode of the battery; during the charge and discharge process of the battery, the dendrites will continue to grow and eventually pierce the diaphragm and contact the positive electrode, causing the battery to fail due to internal short circuit. Hydrogen evolution refers to the decomposition and release of hydrogen by water as an electrolyte solvent during the charge and discharge process of the battery, causing the battery to bloat and even explode. Problems such as dendrites and corrosion of the zinc negative electrode, instability of the electrolyte and hydrogen evolution reaction need to be solved urgently.

[0003] Moisturizer plays a vital role in cosmetic formulas. The quality of cosmetics depends on moisturizers. One of the basic substances that make up cosmetics is moisturizer. Moisturizer is essential in all cosmetic formulas. Moisturizers are roughly divided into four categories: small molecule moisturizers, polymer moisturizers and high-efficiency moisturizers. Common moisturizers include: polyols, oils, sugars, and natural moisturizing factors. The working principles of common moisturizers are: ① moisture absorption, absorbing moisture from the environment to moisturize under normal humidity; ② water lock, mainly closed oil, slowing down the dissipation of moisture in the skin, and cannot directly provide moisture to the skin; ③ biological regulation, mainly regulating the water absorption performance of cells and the lipid barrier structure between cells; ④ film-forming moisturizing, this type mainly includes polysaccharide polymer moisturizers, the aqueous solution swells, combines a large amount of water, has a soft film-forming effect, and generally does not absorb moisture from the skin.

[0004] Hyaluronic acid, sodium pyrrolidone carboxylate, lactic acid and sodium lactate are the main components of the natural moisturizing factor in the human body. Hyaluronic acid is an important component commonly found in the intercellular matrix. Its ability to retain water is stronger than any other natural or synthetic polymer. As a moisturizer, the biggest advantage of hyaluronic acid is its lubricity and film-forming property. After the skin comes into contact with hyaluronic acid, it will combine with water to form a breathable hydrated elastic membrane, which can play a special role in retaining water, making the skin elastic, moisturized and smooth; sodium pyrrolidone carboxylate is a decomposition product of the granular layer silk protein aggregates of the epidermis. The content of sodium pyrrolidone carboxylate in the natural moisturizing factor of the skin is about 12%. When the content of sodium pyrrolidone carboxylate in the stratum corneum decreases, the skin will become dry and rough; lactic acid is the main water-soluble acidic substance in the natural moisturizing factor of the human epidermis, with a content of 12%. The carboxyl group of the lactic acid molecule has a good affinity for hair and skin. Sodium lactate is also a very effective moisturizer, and its moisturizing property is higher than that of glycerol. Lactic acid and sodium lactate form a buffer solution that can adjust the pH value of the skin. Ceramide and collagen are a new generation of moisturizers developed in recent years. They have a similar structure to the materials that make up the stratum corneum of the skin. They can quickly penetrate into the skin and combine with the water in the stratum corneum to form a network structure to fix the moisture. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide an aqueous zinc ion battery electrolyte with an added humectant; another object of the present invention is to introduce the humectant into the zinc ion battery electrolyte, thereby binding water in the electrolyte, inhibiting the occurrence of side reactions in the zinc ion battery, changing the deposition morphology of zinc, and guiding the uniform deposition of zinc, thereby improving the cycle stability and coulombic efficiency of the zinc ion battery.

[0006] Invention idea: The humectant can absorb moisture on the electrode interface in the electrolyte and form a protective film on the electrode interface, which can effectively inhibit the serious dendrite growth, hydrogen evolution, corrosion and other harmful side reactions of the zinc negative electrode in the zinc ion battery caused by water and guide the uniform deposition of zinc.

[0007] To achieve the above purpose, the present invention adopts the following technical scheme: an aqueous zinc ion battery electrolyte with a humectant added, the electrolyte comprising water, a zinc salt and a humectant; the humectant binds water in the electrolyte.

[0008] Further, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, and zinc perchlorate; further, the molar concentration of the zinc salt is 0.5 to 3 mol L -1 .

[0009] Furthermore, the moisturizing agent is selected from one or more of small molecule moisturizing agents and macromolecular moisturizing agents.

[0010] Furthermore, the small molecule moisturizer is selected from one or more of polyol moisturizers, lactic acid or sodium lactate moisturizers, amino acid moisturizers, and vitamin moisturizers.

[0011] Furthermore, the macromolecular moisturizing agent is selected from one or more of hyaluronic acid, polysaccharide moisturizing agents, polypeptide moisturizing agents, and polyethylene glycol.

[0012] Furthermore, the mass concentration of the hyaluronic acid is 5 to 20 mg mL -1 .

[0013] Furthermore, the polypeptide moisturizing agent is selected from collagen, and the mass concentration of the collagen is 50 to 500 mg mL -1 .

[0014] The method for preparing the aqueous zinc ion battery electrolyte with added humectant comprises the following steps: mixing water, zinc salt and humectant to obtain the aqueous zinc ion battery electrolyte with added humectant.

[0015] Application of the above-mentioned aqueous zinc ion battery electrolyte with added humectant in aqueous zinc ion batteries.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The present invention adds a humectant to the electrolyte. The humectant can absorb moisture on the electrode interface in the electrolyte to form a protective film on the electrode interface, which can effectively inhibit the serious dendrite growth, hydrogen evolution, corrosion and other harmful side reactions of the zinc negative electrode in the zinc ion battery caused by water and guide the uniform deposition of zinc, thereby greatly improving the cycle performance and stability.

[0018] (2) The moisturizer is one or more of a small molecule moisturizer and a macromolecular moisturizer. The macromolecular moisturizer is selected from collagen and added to the electrolyte to change the zinc deposition morphology. Zinc is deposited in particles without forming dendrites, and an SEI layer is formed on the surface of the positive electrode, thereby improving the cycle stability and coulomb efficiency of the zinc ion battery. The macromolecular moisturizer is selected from hyaluronic acid. Due to the high molecular weight of hyaluronic acid, it exhibits a steric hindrance effect in the electrolyte, and has a suitable space to buffer the migrating zinc ions, which helps to even out the flow of zinc ions. In addition, the adsorption of the macromolecular moisturizer on the zinc electrode introduces a significant steric hindrance effect, thereby increasing the thickness of the double layer, hindering the electron transfer in the double layer, and delaying the electron transfer in the zinc deposition process, thereby delaying the Faraday process (Zn 2+ Reduction to Zn) avoids the generation of obvious concentration gradients and inhibits dendrite formation;

[0019] (3) The method for preparing the aqueous zinc ion battery electrolyte with the addition of a humectant of the present invention has the advantage of a simple process flow, and the electrolyte is obtained by mixing water, zinc salt and a humectant, which is conducive to promoting the large-scale production and application of zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a comparison chart of the coulombic efficiency of Zn / Cu batteries assembled with the electrolytes of Example 1 and Comparative Example 1 at room temperature;

[0021] Figure 2 This is a scanning electron microscope image of the Cu positive electrode of a Zn / Cu battery assembled with the electrolyte prepared in Example 1 and subjected to electrochemical cycling at room temperature;

[0022] Figure 3 The scanning electron microscope image of the Cu positive electrode of the Zn / Cu battery assembled with the electrolyte prepared in Comparative Example 1 after electrochemical cycling at room temperature;

[0023] Figure 4 (a) is an optical physical image of the electrolytic solution prepared in Example 1 depositing zinc on a copper foil;

[0024] Figure 4 (b) is an optical image of the electrolytic solution prepared in Comparative Example 1 for electrodepositing zinc on a copper foil;

[0025] Figure 5 This is a scanning electron microscope image of the Cu positive electrode of a Zn / Cu battery assembled with the electrolyte prepared in Example 7 and subjected to electrochemical cycling at room temperature;

[0026] Figure 6 The figure is a comparison chart of the coulombic efficiency of Zn / Cu batteries assembled with the electrolytes prepared in Example 7 and Comparative Examples 2 and 3 at room temperature;

[0027] Figure 7 A comparison chart of the coulombic efficiency of Zn / Cu batteries assembled with the electrolytes prepared in Example 7 and Comparative Example 1 at room temperature;

[0028] Figure 8 A comparison chart of the coulombic efficiency of Zn / Cu batteries assembled with the electrolytes prepared in Example 7 and Comparative Example 1 at room temperature;

[0029] Fig. 9 A cycle comparison diagram of a Zn / Zn symmetrical battery assembled with the electrolytes prepared in Example 7 and Comparative Example 1 at room temperature;

[0030] Fig.10 Cycle comparison diagram of Zn / NVO battery assembled with electrolytes prepared in Example 7 and Comparative Example 1 at room temperature. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to be limiting of the present invention.

[0034] The invention discloses a water-based zinc ion battery electrolyte with a humectant added thereto. The electrolyte comprises water, zinc salt and the humectant, and the humectant binds water in the electrolyte.

[0035] The zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, and zinc perchlorate; preferably, the zinc salt is zinc sulfate; and the molar concentration of the zinc salt is 0.5 to 3 mol L -1 .

[0036] The humectant is selected from one or more of small molecule humectants and macromolecular humectants. The humectant is introduced into the zinc ion battery electrolyte. The humectant has the functions of hygroscopicity, water lock and film formation, which can bind water molecules in the electrolyte solution, inhibit the occurrence of side reactions in the zinc ion battery, change the zinc deposition morphology, and guide the uniform deposition of zinc, thereby improving the cycle stability and coulomb efficiency of the zinc ion battery.

[0037] The small molecule moisturizer is selected from one or more of polyol moisturizers, lactic acid and sodium lactate moisturizers, amino acid moisturizers, and vitamin moisturizers; the macromolecular moisturizer is selected from one or more of hyaluronic acid, polysaccharide moisturizers, polypeptide moisturizers, and polyethylene glycol; wherein the mass concentration of hyaluronic acid is 5 to 20 mg mL -1 ; The polypeptide moisturizer is collagen, and the mass concentration of collagen is 50-500 mg mL -1 .

[0038] The present invention also provides a method for preparing the aqueous zinc ion battery electrolyte with the humectant added, comprising the following steps: mixing water, zinc salt and the humectant to obtain the aqueous zinc ion battery electrolyte with the humectant added.

[0039] The present invention will be further described below with reference to the embodiments.

[0040] Example 1

[0041] The aqueous zinc ion battery electrolyte with the addition of humectant in the present embodiment is prepared by the following steps:

[0042] 2.8756 g of zinc sulfate and 0.5 g of collagen were added to 5 mL of water and uniformly dispersed to form a clear mixed solution to obtain an aqueous zinc ion battery electrolyte with a humectant added thereto; wherein the molar concentration of zinc sulfate was 2 mol L -1 , the mass concentration of collagen is 100 mg mL -1 .

[0043] Example 2

[0044] This example is the same as Example 1, except that the mass of zinc sulfate is 0.7189 g and the molar concentration is 0.5 mol L -1 .

[0045] Example 3

[0046] This example is the same as Example 1, except that the mass of zinc sulfate is 1.4378 g and the molar concentration is 1 mol L -1 .

[0047] Example 4

[0048] This example is the same as Example 1, except that the mass of zinc sulfate is 4.3134 g and the molar concentration is 3 mol / L -1 .

[0049] Example 5

[0050] This example is the same as Example 1, except that the mass of collagen is 0.25 g and the mass concentration is 50 mg / mL -1 .

[0051] Example 6

[0052] This example is the same as Example 1, except that the mass of collagen is 2.5 g and the mass concentration is 500 mg / mL -1 .

[0053] Example 7

[0054] The aqueous zinc ion battery electrolyte with the addition of humectant in the present embodiment is prepared by the following steps:

[0055] 2.8756 g of zinc sulfate and 0.05 g of hyaluronic acid were added to 5 mL of water and uniformly dispersed to form a clear mixed solution to obtain an aqueous zinc ion battery electrolyte with a humectant added thereto; wherein the molar concentration of zinc sulfate was 2 mol L-1 , the mass concentration of hyaluronic acid is 10 mg mL -1 .

[0056] Example 8

[0057] This example is the same as Example 7, except that the mass of zinc sulfate is 0.7189 g and the molar concentration is 0.5 mol L -1 .

[0058] Example 9

[0059] This example is the same as Example 7, except that the mass of zinc sulfate is 1.4378 g and the molar concentration is 1 mol L -1 .

[0060] Example 10

[0061] This example is the same as Example 7, except that the mass of zinc sulfate is 4.3134 g and the molar concentration is 3 mol L -1 .

[0062] Comparative Example 1

[0063] The aqueous zinc ion battery electrolyte of this comparative example is prepared by the following steps: 2.8756 g of zinc sulfate is added to 5 mL of water to uniformly disperse it to form a clear mixed solution to obtain an aqueous zinc ion battery electrolyte, wherein the molar concentration of zinc sulfate is 2 mol L -1 .

[0064] Comparative Example 2

[0065] This comparative example is the same as Example 7, except that the mass of hyaluronic acid is 0.025 g and the mass concentration is 5 mg / mL -1 .

[0066] Comparative Example 3

[0067] This comparative example is the same as Example 7, except that the mass of hyaluronic acid is 0.1 g and the mass concentration is 20 mg / mL -1 .

[0068] Experimental test example 1

[0069] This example provides a Zn / Cu battery assembly method, using the aqueous zinc ion battery electrolyte with humectant added prepared in each of the above Examples 1 to 10, and the electrolyte prepared in each of Comparative Examples 1 to 3, as follows:

[0070] The Zn / Cu battery of this experimental test example was assembled by the following method: a CR2032 button battery shell was used, a copper foil with a diameter of 12 mm was used as the positive electrode piece of the zinc ion battery, a zinc sheet with a diameter of 16 mm was used as the negative electrode piece of the symmetrical battery, and glass fiber GF / A was used as a separator. 100 μL of the above-prepared electrolyte was added to the battery to assemble a Zn / Cu battery.

[0071] Experimental test example 2

[0072] This example provides a method for assembling a Zn / Zn symmetrical battery, using the aqueous zinc ion battery electrolyte with humectant added prepared in each of the above Examples 7 to 10, and the electrolyte prepared in each of Comparative Examples 1 to 3, as follows:

[0073] The Zn / Zn symmetrical battery of this experimental test example was assembled by the following method: using a CR2032 button battery case, a zinc sheet with a diameter of 12 mm as the positive electrode sheet of the symmetrical battery, a zinc sheet with a diameter of 16 mm as the negative electrode sheet of the symmetrical battery, and glass fiber GF / A as a separator. 100 μL of the above-prepared electrolyte was added to the battery to assemble a Zn / Zn symmetrical battery.

[0074] Experimental test example 3

[0075] This example provides an assembly method of a Zn / sodium vanadate NVO battery, using the aqueous zinc ion battery electrolyte with humectant added prepared in each of the above Examples 7 to 10, and the electrolyte prepared in each of Comparative Examples 1 to 3, as follows:

[0076] The Zn / NVO battery of this experimental test example was assembled by the following method: using a CR2032 button battery shell, NVO: acetylene black: PVDF (polyvinylidene fluoride) was dispersed in NMP (N-methylpyrrolidone) at a mass ratio of 7:2:1, and each substance was evenly dispersed to form a slurry, which was then dripped onto a stainless steel mesh disc with a diameter of 12 mm and dried to serve as the positive electrode of the zinc ion battery (the average NVO content of a single electrode was about 20 mg cm -1 ); a zinc sheet with a diameter of 16 mm was used as the negative electrode of the symmetrical battery, a glass fiber GF / A was used as the separator, 100 μL of the above-prepared electrolyte was added to the battery to assemble a Zn / NVO battery.

[0077] Figure 1 Comparison of the coulombic efficiency of Zn / Cu batteries assembled with the electrolytes of Example 1 and Comparative Example 1 at room temperature (the current density is 1 mA cm -2 , with a capacity density of 0.5 mAh cm -2), it can be seen that the battery of Example 1 can be stably cycled for more than 400 cycles and maintain a coulombic efficiency of more than 99%, while the battery of Comparative Example 1 cannot be stably cycled and cannot maintain a high coulombic efficiency.

[0078] Figure 2 The scanning electron microscope morphology of the positive electrode sheet of the Zn / Cu battery assembled with the electrolyte of Example 1, Figure 3 The scanning electron microscope morphology of the positive electrode sheet of the Zn / Cu battery assembled with the electrolyte of Comparative Example 1, Figure 2 and Figure 3 By comparison, it can be seen that after long-term cycling, the zinc in the battery of comparative example 1 electrolyte is deposited in the form of spikes, while after long-term cycling, the zinc on the surface of the electrode of the battery of example 1 is deposited in the form of particles without generating dendrites, indicating that adding collagen to the electrolyte can change the morphology of zinc deposition.

[0079] Figure 4 (a) is an optical image of the electrolytic solution prepared in Example 1 depositing zinc on copper foil. Figure 4 (b) is an optical picture of the electrolytic solution prepared in Comparative Example 1 on the copper foil. It can be seen that the surface of the electrolytically deposited zinc on the copper foil of the electrolyte prepared in Example 1 is flat, smooth and light yellow, which is the SEI layer derived from collagen, while the surface of the copper foil of the electrolyte prepared in Comparative Example 1 is rough, and zinc is not deposited in some places, indicating uneven deposition of zinc on the copper foil. The comparison shows that collagen plays a role in the electrolyte.

[0080] Figure 5 The scanning electron microscope morphology of the positive electrode sheet of the Zn / Cu battery assembled with the electrolyte of Example 7 shows that there is no obvious dendrite growth on the electrode sheet and zinc is uniformly deposited.

[0081] Figure 6 The coulomb efficiency comparison chart of Zn / Cu battery assembled with the electrolyte prepared in Example 7, Comparative Example 2 and Comparative Example 3 at room temperature (the current density is 5 mA cm -2 , with a capacity density of 2.5 mAh cm -2 ), it can be seen that the battery of Example 6 can stably cycle more than 500 times and maintain a coulombic efficiency of more than 99%, while the batteries of Comparative Examples 2 and 3 cannot stably cycle and do not maintain a high coulombic efficiency, indicating that hyaluronic acid with a mass concentration of 10 mg / mL plays a better role in the electrolyte.

[0082] Figure 7 and Figure 8 Coulomb efficiency diagram of Zn / Cu battery composed of electrolyte prepared in Example 7 and Comparative Example 1 at room temperature ( Figure 7 The current density is 1 mA cm -2 , with a capacity density of 0.5 mAh cm-2 ; Figure 8 The current density is 5 mA cm -2 , with a capacity density of 2.5 mAh cm -2 ), it can be seen that Example 7 exhibits better cycle stability and higher coulombic efficiency than Comparative Example 1.

[0083] Fig. 9 Cyclic comparison of Zn / Zn symmetrical cells assembled with the electrolytes prepared in Example 7 and Comparative Example 1 at room temperature (with a current density of 20 mA cm -2 , with a capacity density of 5 mAh cm -2 ), it can be seen that the battery of Example 7 can stably cycle more than 600 times at room temperature, while the battery of Comparative Example 1 cannot stably cycle, indicating that hyaluronic acid plays a role in the electrolyte of Example 7.

[0084] Fig.10 Cyclic comparison of Zn / NVO battery assembled with electrolytes prepared in Example 7 and Comparative Example 1 at room temperature (current density is 0.5Ag -1 The NVO loading of a single cathode sheet is about 20 mg cm -1 ), it can be seen that the battery of Example 7 still maintains high discharge capacity, capacity retention rate and coulombic efficiency after 250 cycles, showing better cycle stability than the battery of Comparative Example 1.

[0085] It can be seen that the moisturizer has the functions of absorbing moisture, locking water and forming a film. It can bind the water molecules in the electrolyte solution, inhibit the occurrence of side reactions in zinc-ion batteries, change the deposition morphology of zinc, and guide the uniform deposition of zinc, thereby improving the cycle stability and coulombic efficiency of zinc-ion batteries.

[0086] The method is simple to prepare, the raw materials are cheap and readily available, and it is suitable for large-scale production, and has good application prospects.

[0087] The electrolytes of Examples 1 to 10 and Comparative Examples 1 to 3 were assembled into Zn / Cu batteries for battery performance testing. The results are listed in Table 1.

[0088] Table 1 Battery test performance of Zn / Cu batteries assembled with electrolytes of Examples 1 to 10 and Comparative Examples 1 to 3 at room temperature

[0089]

[0090] It can be seen from Table 1 that they still maintain a high coulombic efficiency after 400 cycles, especially Example 1 and Example 7 can maintain a very high coulombic efficiency. Example 7 can still maintain a coulombic efficiency of 99.06% after 1000 cycles of stable circulation. It can be seen that the battery prepared by the electrolyte with the addition of humectant has good cycle performance and safety performance.

[0091] The moisturizing agent of Example 7 is hyaluronic acid HA, and the effects of HA are as follows: (1) the presence of HA in the electrolyte leads to competition for hydrogen bonds between HA and H2O molecules, resulting in a reduction in hydrogen bonds between H2O and H2O; due to the highly interconnected hydrogen bond network in the HA electrolyte, the activity of water is reduced, the electrochemical stability is improved, and the reactivity of H2O is effectively inhibited, resulting in a lower HER potential and inhibition of hydrogen evolution reaction. At the same time, the OER potential is also increased and the oxygen evolution reaction is also inhibited; (2) The molecular weight of hyaluronic acid is 1000000 to 1500000 Daltons, which shows a steric hindrance effect in the electrolyte. There is a suitable space to buffer the migrating zinc ions, which helps to uniform the flow of zinc ions. In addition, the adsorption of the macromolecular moisturizer on the zinc electrode introduces a significant steric hindrance effect, thereby increasing the thickness of the double layer, hindering the electron transfer in the double layer, and delaying the electron transfer during zinc deposition, thereby delaying the Faraday process (Zn 2+ reduced to Zn), avoiding the formation of obvious concentration gradients and inhibiting dendrite formation; (3) Negatively charged hyaluronic acid molecules weaken the Zn 2+ With H2O or SO4 2- The electrostatic force between Zn 2+ The dissolution of Zn makes the charge distribution on the Zn surface uniform, guides the uniform deposition of Zn, and thus prevents the formation of Zn dendrites.

[0092] The moisturizer of Example 1 is collagen, which can change the deposition morphology of zinc and guide the uniform deposition of zinc. Since the molecular weight of collagen is 1000 Daltons, the steric hindrance effect exhibited in the electrolyte is slightly inferior to that of hyaluronic acid, but it may be because it can guide zinc ions to deposit uniformly in granular form without generating dendrites, and also exhibits excellent cycle stability and coulombic efficiency.

[0093] In Comparative Example 2, the HA in the hyaluronic acid is too little, and the HA does not fully interfere with the highly interconnected hydrogen bond network between water molecules. The activity of water is still relatively large, and the reactivity of hydrogen and oxygen evolution is relatively large. These harmful reactions affect the long life of the battery. In addition, the HA is too little, resulting in a small amount of hyaluronic acid molecules adsorbed on the Zn electrode without sufficient steric hindrance effect, resulting in excessive metal reduction during the deposition process, which depletes the Zn on the electrode surface. 2+ , resulting in a concentration gradient, which intensifies the formation of dendrites and affects the long life of the battery. 2+ With water or SO42- The electrostatic force between them is strong, the solvated structure is stable, and hyaluronic acid only weakens a small part of Zn 2+ With water or SO4 2- The electrostatic force between the Zn 2+ The desolvation is slow, resulting in more Zn 2+ Incomplete desolvation, residual H2O / SO4 on the Zn surface 2- , more by-products are generated, which cause dendrite formation and pierce the separator, resulting in the battery being unable to have a long cycle life.

[0094] In comparative example 3, there is too much hyaluronic acid, and a large number of hyaluronic acid molecules accumulate on the electrode surface, resulting in too much increase in the thickness of the double electric layer. The electron transfer rate during the galvanizing process is too slow, that is, the viscosity of the electrolyte increases, the ionic conductivity decreases, and the kinetics is too slow, which makes the battery unable to have a long life cycle.

[0095] The electrolytes prepared in Examples 7 to 10 and Comparative Examples 1 to 3 were assembled into Zn / NVO batteries for battery performance testing. The results are listed in Table 2.

[0096] Table 2 Battery test performance of Zn / NVO batteries assembled with electrolytes of Examples 7 to 10 and Comparative Examples 1 to 3 at room temperature

[0097]

[0098]

[0099] It can be seen from Table 2 that the Zn / NVO batteries assembled with the electrolytes prepared in Examples 7 to 10 can maintain a relatively high capacity after 150 cycles, and have good cycle performance and safety performance.

[0100] In summary: the skin care and moisturizing cosmetic material of the present invention has the functions of hygroscopicity, water locking and film-forming, can bind water molecules in the electrolyte solution, inhibit the occurrence of side reactions in the zinc ion battery, change the deposition morphology of zinc, and guide the uniform deposition of zinc, thereby improving the cycle stability and coulomb efficiency of the zinc ion battery.

[0101] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte with added humectant, characterized in that: The electrolyte includes water, zinc salt and humectant; the humectant binds the water in the electrolyte.

2. The aqueous zinc ion battery electrolyte with added humectant according to claim 1, characterized in that: The zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, and zinc perchlorate; the molar concentration of the zinc salt is 0.5 to 3 mol L -1 .

3. The aqueous zinc ion battery electrolyte with added humectant according to claim 1, characterized in that: The moisturizing agent is selected from one or more of small molecule moisturizing agents and macromolecular moisturizing agents.

4. The aqueous zinc ion battery electrolyte with added humectant according to claim 3, characterized in that: The small molecule moisturizer is selected from one or more of polyol moisturizers, lactic acid or sodium lactate moisturizers, amino acid moisturizers, and vitamin moisturizers.

5. The aqueous zinc ion battery electrolyte with added humectant according to claim 3, characterized in that: The macromolecular moisturizing agent is selected from one or more of hyaluronic acid, polysaccharide moisturizing agents, polypeptide moisturizing agents, and polyethylene glycol.

6. The aqueous zinc ion battery electrolyte with added humectant according to claim 5, characterized in that: The mass concentration of the hyaluronic acid is 5 to 20 mg mL -1 .

7. The aqueous zinc ion battery electrolyte with added humectant according to claim 5, characterized in that: The polypeptide moisturizing agent is selected from collagen, and the mass concentration of the collagen is 50-500 mg mL -1 .

8. The method for preparing the aqueous zinc ion battery electrolyte with added humectant according to claim 1, characterized in that: The method comprises the following steps: mixing water, zinc salt and a moisturizing agent to obtain the aqueous zinc ion battery electrolyte with the moisturizing agent added thereto.

9. Use of the aqueous zinc ion battery electrolyte containing a humectant as claimed in any one of claims 1 to 7 in an aqueous zinc ion battery.

Citation Information

Cited By

  • Zinc ion battery electrolyte containing polysaccharide zinc chelate as well as preparation method and application of zinc ion battery electrolyte

    CN120221824A